A systematic review of post COVID-19 condition in children and adolescents: Gap in evidence from low-and -middle-income countries and the impact of SARS-COV-2 variants - Nina Dwi Putri; Ida Safitri Laksanawati; Dominicus Husada; Nastiti Kaswandani; Ari Prayitno; Rina Triasih; Irma Sri Hidayati; Retno Asih; Robby Nurhariansyah; Fabiola Cathleen; Dwiana Ocviyanti; Sri Rezeki Hadinegoro; et al. (PLoS ONE, 2025)
The long-term health consequences following COVID-19 have largely been reported in adult populations living in high-income countries. We therefore did a systematic review of post COVID-19 condition symptoms reported in children and adolescents (<18 years), aiming to identify and include publications from low- or middle-income countries (LMICs). From EMBASE, Medline, and Pubmed until the 30th of October 2023, we searched all studies reporting original and complete data of long-term outcomes of at least 20 children or adolescents under 18 years of age with a history of confirmed acute COVID-19 infection. We excluded non-English publications, pre-prints, unreviewed articles, grey literature, studies with inaccessible full text, and those limited to a specific population. Risk of Bias was assessed using STROBE guidelines for observational studies. We used descriptive narrative analysis to summarize the findings. Forty studies reporting 825,849 children and adolescents; the median age of those with persistent symptoms was consistently in the adolescent age range but not all studies included young children (<5 years). Only one study, with 58 participants aged 6-17 years, population was from a LMIC. Studies relied on symptom reporting rather than objective measures of organ dysfunction. The definition of post COVID-19 condition varied; most studies used persistent symptom duration of two or three months or more. However, since the symptom onset was not specified, it was difficult to identify which study is truly consistent with WHO’s definition of post COVID-19 condition. Prevalence of post COVID-19 condition ranged from 1.8% to 70% but with marked heterogeneity between study populations and reporting criteria including the severity of acute COVID presentation. Most studies were undertaken when the Alpha variant was the predominant strain. The prevalence of post COVID-19 condition ranged from 6.7% to 70% in the Alpha variant-, 23% to 61.9% in the Delta-, 17% to 34.6% in the Omicron-, and 3.7% to 34% in the Other-variant predominated studies. The most reported symptoms were fatigue (70%), headache (37.5%) and respiratory symptoms (35%); fatigue was most reported in all variant subgroups. Only half of the studies included a control group. The variations in study population, reporting methods, reliance on symptom reporting alone and lack of control groups make it challenging to determine the impact of COVID-19 on post COVID health in children and adolescents. The lack of data from LMIC populations especially infants and young children is a major gap.